Berkurban dengan Uang; Kajian Kritis Terhadap Hadis-hadis Berqurban - Abdurrahman, Zulkarnain (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2022)
Recently there has been an opinion that the implementation of sacrificial worship does not have to be in the form of slaughtering sacrificial animals but may be replaced in the form of money equivalent to the purchase price of the sacrificial animal as is the case in the case of zakat fitrah. This method of sacrificing is considered easier and more beneficial for Muslims than having to distribute it in the form of meat. The above opinion at a glance is very relevant and responsive to the problems that are being faced by Muslims. But what is the view of Islamic law regarding the above problems? Is the sacrifice included in the category of ghair ma’qul al-ma’na worship so that in its implementation it must follow the procedures that have been confirmed in the Qur’an and hadith, namely by slaughtering the sacrificial animal or is it included in the ma’qul al-ma’na category so that it can be sacrificed? analogized and replaced in the form of money?